TRIPATRI KONSEP DASAR PENGHAPUS POTRET BURAM KUALITAS PENDIDIKAN SENI - I Ketut Sunarya (Jurnal Cakrawala Pendidikan, 2004)
Success ofa tertiary educational institution ofart is not merely measured from the quality ofstudents graduated, but also from the quatity of students absorbed in the work fieds. By absorbed it means not merely to be accommodated, but furthermore to be able to create new work fields. What occurs nowadays, in the contrary, is the decline ofthe quality ofhuman resources which is releted with the quality ofeduca tion art. Tbis is not apart from the responsibility ofthe tertiary educa tion art as the institution which provides the humanreseurces. Seeing this reality the three intact and united points oftripatri as the basic concept ofhuman resources quality increase needs to be examined. First; a conduccive campus is not limited merely to the software such as behavior control, communication system, a clear and aimed cur riculum, clear description ofassignments, etc. Italso includes the struc turing ofthe harware like phycal environment which wi] enable all the elements involved to focus and participate completely in an academic activity. Secondly, the qualified lecturers willing to work hard and to endeavor at all times to increase his kenowledge and also to become conscious ofhis duty in filing and developing his mission tri dhanna. Thirdly, creative students, is the main element in bringging into reality the qualified generation which independently isable the create the taks for himselfin order to be able to gather the maximum benefits. In the and, the ojective oftripatri concepti is to incease the ability ofthe students as the young generation and the nation hope which in the comprehension and the performance not simply act as the man ofanalysis but also as man ofsynthesis in ofart. Keywords: The Role ofTertiary Educational Institutionofart in Increasing the Quality of Young Generation.